Charge Nurses Taking Charge, Challenging the Culture of Culture-Negative Sepsis, and Preventing Central-Line Infections to Reduce NICU Antibiotic Usage - Shukla, Samarth; Cortez, Josef; Renfro, Bill; Makker, Kartikeya; Timmons, Colleen; Nandula, P. Sireesha; Hazboun, Rita; Dababneh, Rima; Hoopes, Cristina; VanRavestein, Jenny; McCarter, Yvette; Middlebrooks, Marilyn; Ingyinn, Ma; Alvarez, Ana; Hudak, Mark L. (American Journal of Perinatology, 2020)
Objective We aimed to reduce our monthly antibiotic usage rate (AUR, days of treatment per 1,000 patient-days) in the neonatal intensive care unit (NICU) from a baseline of 330 (July 2015–April 2016) to 200 by December 2018.Study Design We identified three key drivers as follows: (1) engaging NICU charge nurses, (2) challenging the culture of culture-negative sepsis, and (3) reducing central-line associated bloodstream infections (CLABSI). Our main outcome was AUR. The percentage of culture-negative sepsis that was treated with antibiotics for >48 hours and CLABSI was our process measure. We used hospital cost/duration of hospitalization and mortality as our balancing measures.Results After testing several plan-do-study-act (PDSA) cycles, we saw a modest reduction in AUR from 330 in the year 2016 to 297 in the year 2017. However, we did not find a special-cause variation in AUR via statistical process control (SPC) analysis (u'-chart). Thereafter, we focused our efforts to reduce CLABSI in January 2018. As a result, our mean AUR fell to 217 by December 2018. Our continued efforts resulted in a sustained reduction in AUR beyond the goal period. Importantly, cost of hospitalization and mortality did not increase during the improvement period.Conclusion Our sequential quality improvement (QI) efforts led to a reduction in AUR. We implemented processes to establish a robust antibiotic stewardship program that included antibiotic time-outs led by NICU charge nurses and a focus on preventing CLABSI that were sustained beyond the QI period.Key Points
Keywords: antibiotic usage rate; central-line infection; quality improvement